INFORMATION TECHNOLOGY AND UTILIZATION OF FINANCIAL INFORMATION SYSTEMS ON THE EFFECTIVENESS OF ACCOUNTING INFORMATION SYSTEMS IN COOPERATIVES - Ghonimah Zumroatun Ainiyah; Kartika Dewi Permatasari; Siti Murwati; Yuce Sariningsih; Siti Patimah (Universitas Pasundan, 2022)
The purpose of this study was to determine information technology and the use of financial information systems on the effectiveness of accounting information systems in cooperatives, especially in Purwareja Klampok and Mandiraja districts. This type of research is quantitative research by distributing questionnaires directly to managers and the finance department of cooperatives in the two sub-districts. The population of this research is the manager and the finance department as many as 80 people. The sample in this study was taken 80 people. The data analysis technique used multiple linear regression. Quantitative analysis in this study will use validity and reliability tests with Cronbach's Alpha. Classical assumption test includes normality test, multicollinearity test and heteroscedasticity test. The results show that information technology and the use of financial information systems have a significant and significant effect on accounting information systems as evidenced by the results of the calculation of the SPSS application program, the R value of the two variables is 0.806 while the coefficient of determination is 0.650 (65%) meaning that the percentage of the influence of information technology variables and utilization of financial information systems by 65% ​​and the remaining 35% is influenced by other variables that are not included in this study. Keywords: Information Technology and Utilization of Financial Information Systems.